Synthetic, organic fertilization and biofertilizers in tomato (Solanum lycopersicum L.) cultivation in greenhouse (Bioagro, 2026)
Tomato crop in protected environments relies primarily on synthetic fertilizers. This research evaluated the effect of synthetic, organic, and biofertilizer fertilization on chlorophyll index, growth variables, and fruit production and quality in tomato plants grown under greenhouse conditions. The experimental design was a randomized complete block design with a factorial arrangement, and two factors were evaluated: i) fertilization, with the following levels: application of synthetic fertilizers, using Steiner nutrient solution at 100 % (SN100) and 50 % (SN50) concentrations; application of organic fertilizer (FO); and its combination with synthetic fertilization at 50 % (SN50 + FO); and ii) biofertilization with the consortium Azospirillum brasilense, Bacillus subtilis, and Glomus intraradices. The levels were application at sowing (BS), at transplanting (BT), at sowing and transplanting (BST), and without inoculation (SM). With the control (SN100 x SM), plants showed greater growth, yield, and fruit quality. With 50 % mineral fertilization (SN50), values were lower than the control, but the lowest yield was observed with FO. No differences were found in the biofertilizer factor. With the interaction SN50 + FO x BST (50 % nutrient solution, organic fertilization, and inoculations at planting and transplanting), fruit yield was statistically equal to the control. Therefore, it is concluded that this interaction is an alternative for maintaining the productivity of tomato crops in intensive systems.
Keywords: Azospirillum brasilense; Bacillus subtilis; Glomus intraradices; organic fertilizers; nutrient solution